(untitled) (Global Journal of Science Frontier Research, 2015)
In this paper we introduce the definition of fuzzy distance space on fuzzy set then we study and discuss several properties of this space after some illustrative examples are given. Furthermore we introduce the definition of fuzzy convergence, fuzzy Cauchy sequence of fuzzy point and fuzzy bounded fuzzy distance space.